Transformasi Corporate Identity PT BGR Logistik Indonesia dalam Perspektif Public Relations - Alam, Fadhli Noor; Chaerowati, Dede Lilis; Wiwitan, Tresna (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Corporate identity transformation is a crucial aspect of business strategy, especially in the context of mergers and corporate restructuring. This research discusses the corporate identity transformation process of PT BGR Logistik Indonesia as part of the IDFood Group, focusing on logo changes and communication strategies from a Public Relations (PR) perspective. This research uses a qualitative method with a case study approach to explore how the logo transformation is not only a visual change but also a representation of the company's values and strategies. The results showed that PT BGR Logistik Indonesia maintained the old logo elements as a differentiation strategy, maintaining a widely recognized brand identity. This transformation process demands an effective PR communication strategy to ensure optimal acceptance from stakeholders. The communication strategy includes internal socialization to employees and external to customers and business partners through social media, press releases, and company events. This research concludes that the transformation of PT BGR Logistik Indonesia's corporate identity not only impacts the company's image but also builds identity continuity amid change. PR communication strategy plays an important role in maintaining consistency and public trust in the company amid the dynamics of the logistics industry.